FAP-a and GOLPH3 Are Hallmarks of DCIS Progression to Invasive Breast Cancer - Yu, Li-Na; Liu, Zhen; Tian, Yan; Zhao, Pei-Pei; Hua, Xing (Frontiers in Oncology, 2019)
Biological markers that could predict the progression of ductal carcinoma in-situ (DCIS) to invasive breast cancer (IDC) are required urgently for personalized therapy for patients diagnosed with DCIS. As stroma was invaded by malignant cells, perturbed stromal-epithelial interactions would bring about tissue remodeling. With the specific expression of the fibroblast activation protein-alpha (FAP-a), Carcinoma-associated fibroblasts (CAFs) are the main cell populations in the remodeled tumor stroma. Golgi phosphoprotein 3 (GOLPH3), a documented oncogene possessing potent transforming capacity, is not only up-regulated in many tumors but also an efficient indicator of poor prognosis and more malignant tumors. The present study aimed to retrospectively evaluate the pathological value of FAP-a and GOLPH3 in predicting the recurrence or progression of DCIS to invasive breast cancer. Immunohistochemical techniques were applied to investigate the expression of FAP-a GOLPH3 in 449 cases of DCIS patients received extensive resection and with close follow-up, but not being treated with any form of chemo- or radio-therapy. The combination of FAP-a and GOLPH3 in predicating the recurrence or progression of DCIS into invasive breast cancer was specifically examined. The study demonstrated that the overexpression of FAP-a in stromal fibroblasts and GOLPH3 in carcinoma cells are highly predictive of DCIS recurrence and progression into invasive breast cancer. Both FAP-a and GOLPH3 have high specificity and sensitivity to predict the recurrence of DCIS. Moreover, the combination of FAP-a and GOLPH3 tends to further improve the specificity and sensitivity of DCIS recurrence by 9.72–10.31 and 2.72–3.63%, respectively. FAP-a and GOLPH3 serve as novel markers in predicting the recurrence or progression of DCIS into invasive breast cancer.